PENGARUH MEDIA CARD SORT TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS X PADA MATERI KLASIFIKASI TUMBUHAN (PLANTAE) DI SMA NEGERI 2 NARMADA KABUPATEN LOMBOK BARAT - Sri Andayani; M Harja Efendi; Firman Ali Rahman (Jurnal Inovasi Pendidikan dan Sains, 2023)
This study aims to determine the effect of card sort learning media on critical thinking skills and student learning outcomes. The type of research used is quasi-experimental. The research was conducted at SMA Negeri 2 Narmada for the academic year 2022/2023. The results showed that the critical thinking skills of students who used card sort media obtained an average score of 65.81 and the critical thinking skills of students who did not use card sort learning media obtained an average score of an average of 59.87 while for learning outcomes using card sort learning media obtained an average score of 83.23 and those who did not use card sort learning media obtained an average score of 74.19. so that it can be stated that card sort learning media has an effect on critical thinking skills and student learning outcomes. In conclusion, there is a significant difference in the ability to think critically and the learning outcomes of class X SMA Negeri 2 Narmada in the 2022/2023 academic year between learning using card sort and direct learning.